Occurrence and diffusive air-seawater exchanges of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in Fildes Bay, King George Island, Antarctica - Luarte, Thais; Hirmas-Olivares, Andrea; Höfer, Juan; Giesecke, Ricardo; Mestre, Mireia; Guajardo-Leiva, Sergio; Castro-Nallar, Eduardo; Pérez-Parada, Andrés; Chiang, Gustavo; Lohmann, Rainer; Dachs, Jordi; Nash, Susan Bengtson; et al. (Elsevier, 2024)
We report the levels of organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) in seawater and air, and the air-sea dynamics through diffusive exchange analysis in Fildes Bay, King George Island, Antarctica, between November 2019 and January 30, 2020. Hexachlorobenzene (HCB) was the most abundant compound in both air and seawater with concentrations around 39 ± 2.1 pg m-3 and 3.2 ± 2.4 pg L-1 respectively. The most abundant PCB congener was PCB 11, with a mean of 3.16 ± 3.7 pg m-3 in air and 2.0 ± 1.1 pg L-1 in seawater. The fugacity gradient estimated for the OCP compounds indicate a predominance of net atmospheric deposition for HCB, α-HCH, γ-HCH, 4,4'-DDT, 4,4'-DDE and close to equilibrium for the PeCB compound. The observed deposition of some OCs may be driven by high biodegradation rates and/or settling fluxes decreasing the concentration of these compounds in surface waters, which is supported by the capacity of microbial consortium to degrade some of these compounds. The estimated fugacity gradients for PCBs showed differences between congeners, with net volatilization predominating for PCB-9, a trend close to equilibrium for PCB congeners 11, 28, 52, 101, 118, 138, and 153, and deposition for PCB 180. Snow amplification may play an important role for less hydrophobic PCBs, with volatilization predominating after snow/glacier melting. As hydrophobicity increases, the biological pump decreases the concentration of PCBs in seawater, reversing the fugacity gradient to atmospheric deposition. This study highlights the potential impacts of climate change, through glacier retreat, on the biogeochemistry of POPs, remobilizing those compounds previously trapped within the cryosphere which in turn will transform the Antarctic cryosphere into a secondary source of the more volatile POPs in coastal areas, influenced by snow and ice melting. This study was funded by ANID/FONDECYT/Regular 1161504 (KP), ANID/FONDECYT/Regular 1210946 (CGM), ANID-PIA-INACH-ACT192057 (CGM, ECN), INACH REGULAR RT_12_17 ...